2022
DOI: 10.1007/s00296-022-05100-9
|View full text |Cite
|
Sign up to set email alerts
|

Overview of infections as an etiologic factor and complication in patients with vasculitides

Abstract: Vasculitides, a form of inflammatory autoimmune disease targeting the vessels, constitute an entity with significant morbidity and mortality. Infections have long been associated with vasculitides as a result of the incident immunosuppression following treatment induction and maintenance. Several microbial pathogens have been described as etiologic factors of infections in this patient population according to the type of vessels affected. Intense research has also been recently conducted in the interplay betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 100 publications
0
8
0
Order By: Relevance
“…For the clusters of 'Increased urate' and 'Increased inflammation,' the top traits were confirmed by the PheWAS. CKD is also associated with dyslipidemia comprising high levels of triglycerides and LDL-cholesterol, and low levels of HDL-cholesterol and apolipoprotein A1 [29] . We could observe similar associations in clusters 'Increased inflammation,' 'Reduced lipids,' and 'Reduced inflammation.'…”
Section: Discussionmentioning
confidence: 99%
“…For the clusters of 'Increased urate' and 'Increased inflammation,' the top traits were confirmed by the PheWAS. CKD is also associated with dyslipidemia comprising high levels of triglycerides and LDL-cholesterol, and low levels of HDL-cholesterol and apolipoprotein A1 [29] . We could observe similar associations in clusters 'Increased inflammation,' 'Reduced lipids,' and 'Reduced inflammation.'…”
Section: Discussionmentioning
confidence: 99%
“…The strength and temporal pattern of the association between sepsis and increased risk of IMIDs suggest a causal relationship. Some IMIDs have been associated with specific pathogens, such as SLE and MS with Epstein-Barr virus, or polyarteritis nodosa with hepatitis B [16,[45][46][47]. The association between sepsis and IMIDs onset appeared well balanced across pathogen categories and viruses, bacteria, and parasites all induce multiple inflammatory cascades leading to the activation of innate and adaptive immune cells [48].…”
Section: Discussionmentioning
confidence: 99%
“…Incidences are presented per 100,000 patient-years. IMID incidences in general population, as reported in literature is presented as references[36][37][38][39][40][41][42][43][44][45][46][47][48]. AIHA, autoimmune hemolytic anemia; AAV, ANCAassociated vasculitis; ANCA, anti-neutrophil cytoplasmic antibody; BD, Behçet's disease; GCA, giant cell arteritis; IBD, inflammatory bowel disease; IMIDs, immune-mediated inflammatory diseases; ITP, immune thrombocytopenia; MS, multiple sclerosis; PMR, polymyalgia rheumatic; RA, rheumatoid arthritis; SLE, systemic lupus erythematosus; SS, Sjögren's syndrome; SSs, systemic sclerosis.…”
mentioning
confidence: 99%
“…Infection can also trigger vasculitis through a variety of mechanisms, including the activation of autoreactive B and T cells, direct invasion of endothelial cells, cell-mediated type IV hypersensitivity, and immune complex-mediated vascular damage, including formation of ANCA ( 4 ). Recent studies have revealed various pathogenic mechanisms for ANCA formation during infection ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study from Taiwan reported that infection-associated HLH is mostly caused by viruses (41%) but occasionally by mycobacteria (23%), bacteria (23%), and fungi (13%), with a high mortality rate without appropriate pathogen-specific therapy ( 2 ). In contrast, the association between infections and the formation of anti-neutrophil cytoplasmic antibodies (ANCAs) has been known for decades ( 3 , 4 ). A fraction of patients with infection-triggered ANCAs develop ANCA-associated vasculitis (AAV) ( 5 ).…”
Section: Introductionmentioning
confidence: 99%